Effects of Borneol on Pharmacokinetics and Tissue Distribution of Notoginsenoside R1 and Ginsenosides Rg1 and Re in Panax notoginseng in Rabbits - Shixiang Wang; Weijin Zang; Xinfeng Zhao; Weiyi Feng; Ming Zhao; Xi He; Qinshe Liu; Xiaohui Zheng (Journal of Analytical Methods in Chemistry)
The purpose of this study is to investigate the effects of Borneol on the pharmacokinetics of notoginsenoside R1 (NGR1) and the ginsenosides Rg1 (GRg1) and Re (GRe) in Panax notoginseng. Reversed phase high-performance liquid chromatography coupled with electrospray ion trap mass spectrometry was employed to determine the concentrations of the three compounds in rabbit plasma. In comparison with rabbits administrated Panax notoginseng extract alone, animals simultaneously taking Panax notoginseng extract and Borneol exhibited significant differences in pharmacokinetic parameters of NGR1, GRg1, and GRe, such as increasing their bioavailability. Quantities of NGR1, GRg1, and GRe in rabbit tissues were also increased after combining administration of Borneol. In addition, the apparent permeability coefficients (Papp) of NGR1, GRg1, and GRe were raised by Borneol significantly in Caco-2 cells. However, no significant changes were observed in the efflux ratio (Er) of NGR1, GRg1 and GRe. These data indicate that Borneol has the properties of enhancing the intestinal absorption, increasing the distribution, and inhibiting the metabolism of NGR1, GRg1, and GRe. The underlying mechanism might be attributed to the loosening of the intercellular tight junction.